EFEKTIVITAS PEMBELAJARAN - ROHMAWATI, AFIFATU (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The purpose of this study is to obtain information about the effectiveness of learning in class A2 Kindergarten Miftahul Huda Kecamatan Turen Kabupaten Malang. The study uses qualitative research approach with case study method using data analysis models Milles and Huberman. Based on the research findings show that: (1) learning is effective because of the conditioning that is done continuously between the vision and mission of the school in achieving quality education, (2) the existence of readiness of teachers in planning learning and teachers' attitudes and capabilities in provide exemplary in children, (3) the success of parents in achieving effective learning in children can not be separated from their parents upbringing influenced by socio-economic background of the family as well as the intensity of the time spent with the child, (4) the awareness of society in school success petrified organize effective learning, (5) the shape is done with the cooperation of stakeholders to establish communication and involvement in school activities. Keywords: effectiveness of learning, Kindergaeden, teacher attitudes